Banking Sector Reforms and Economic Growth: Recent Evidence from a Reform-Bound Economy - Bernhard O Ishioro (Binus Business Review, 2017)
This research investigated the banking sector reforms and economic growth using time series data from 1970 to 2013 for the Nigerian economy. Autoregressive Distributed Lags (ARDL) Bounds test was applied for the specific determination of the long and short-run relationships between banking sector reforms and economic growth. The research finds that the interest rate margin is more significant than other variables in the model in explaining the banking sector reforms and economic growth. Banking sector credit to the private sector was negative and statistically insignificant in economic growth in Nigeria. This means that the size of the banking sector does not enhance economic growth. Meanwhile, inflation is negatively and statistically significant in economic growth. The duration of banking sector reforms should be defined and strictly adhered to irrespective changes in the political administration of the country.